Knowledge and beliefs of the city dwellers regarding dengue transmission and their relationship with prevention practices in Dhaka city, Bangladesh - Kabirul Bashar (Public Health in Practice, 2020)
Objectives: The objectives of the study were to explore knowledge, attitudes, and practice (KAP) of dengue fever among Dhaka city dwellers and the potential associated factors. Study design: A cross-sectional survey was conducted among the city dwellers in Dhaka north and south city corporations using a standardized questionnaire from November to December 2019. Methods: Households were selected by purposive sampling and interviewed face to face by the trained interviewers. The association between education and occupation with the dengue practice was tested using the chi-square test statistic. Results: Around 96% of respondents claimed that they heard about Dengue, and 80% of them correctly identified its causes. Nearly half of the people did not know the breeding season and ecology of dengue vector mosquitoes. Though the city dwellers were well-known about Dengue’s burden, they were reluctant to take preventive measures to get rid of this disease. More than 70% of people mentioned that every family member regularly sleeps under a bed net. Moreover, we found a significant relationship between the education level (p<0.05), as well as the occupation of the respondents (p<0.05) with the practice to prevent and control Dengue. We did not find any information, education, and communication (IEC) activities in the city during our survey. Conclusion: Many people didn’t know the specific preventive measures to minimize potential exposure to Dengue. This lack of knowledge is likely due to inadequate coverage with IEC activities. So, IEC intervention programs may need to start soon in highly dengue-endemic cities to reduce the burden.